Hubungan Pemerintah Daerah dengan DPRD Kabupaten Kuantan Singingi dalam Penetapan APBD Tahun 2017 - Zulfa Harirah MS; Fhisilmi Kaffah (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2020)
Determination of the budget and regional expenditure income (APBD) of Kuantan Singingi Regency has a polemic in the formulation process. The delay in the enactment of this regional budget regulation indicates that there is a bad relationship between the regional head and the Kuantan Singingi district parliament. To answer the problems that occur, an analysis is conducted to find the bright spots of the polemic. This research was conducted to see the relationship between the DPRD and local government in the process of formulating the APBD. This research uses a qualitative approach. Data collection techniques namely by studying literature and using previous research. This study uses Stone's interaction type theory, namely decisional type, anticipated reaction type, non-decisional making type, systemic type. The results showed that the relationship between the local government and the Regional Parliament of Kuantan Singingi in the formulation of the 2017 Regional Budget was included in the type of non-decessional making interaction. This type of interaction is a form of interaction that is influenced by the presence of a strong majority group in influencing the process of formulating the APBD, especially on the submission and agreement of the KUA-PPAS by providing public issues so that a bad image is formed.